O CONTROLE SOCIAL NA PERSPECTIVA DO SISTEMA ÚNICO DE ASSISTÊNCIA SOCIAL (SUAS): análise do Conselho Municipal de Assistência Social de São Luís (MA) - Fróes, Adriana Lígia Alvarenga Oliveira (2013)
This thesis is a study of social control from the perspective of Unified Social Assistance System (ITS) in order to perform an analysis of the performance of the Municipal Council of Social Service of São Luís (MA), considering that the space Councils while instances of social control of public policies have contributed over the years, with participatory processes involving different social subjects, inserted in various areas of struggle for rights guaranteed. As this analysis of the social control of Social Policy, in São Luís, we start from a theoretical-conceptual on Social Policy, social control, participation, Social Assistance Policy in Brazil and Maranhao as well as the configuration of ITS in Brazil and Maranhao. The study aimed to analyze the performance of the City Council of Social Welfare in São Luís (MA), with emphasis on the dynamics of formation, structure, possibilities and limits, as a forum for social control within the Social Care in St. Louis (MA). Besides this analysis, our study has proposed some challenges for the strengthening of social control within the City Council Social Services of St. Louis (MA), understanding the difficulties that occur within this Council and that the relations between state and civil society in this process are built collectively with bumps, discussions, a balance of forces, which aims to fight for rights and democratization of public policy.